Being in the right place: A natural field experiment on the causes of position effects in individual choice - Harris, Mark; Novarese, M.; Wilson, C.M. (ELSEVIER, 2022)
This paper aims to better understand why individuals tend to select items at the top of lists. Within a natural field experiment, we randomize the order in which new economics research papers are presented in email alerts and measure the subsequent download activity. Our novel disaggregate data allows us to evidence i) how position effects vary across users, ii) the order in which users select their items, and iii) how position effects are related to users’ selection orders. Overall, the findings are most consistent with an explanation of choice fatigue where users consider the listed items in a downwards-then-upwards order.